Direct Recovery of Recombinant Hepatitis B Core Antigen from Unclarified Escherichia Coli Feedstock Using Expanded Bed Adsorption Chromatography - Ng, Michelle Yeen Tan (2008)
The capsid of hepatitis B virus (HBV), which consists of hepatitis B core antigen (HBcAg) has become one of the most frequently studied viral-like-particle (VLP) for the display of foreign epitopes. Many studies have been carried out to purify this capsid. However, the conventional method of purification requires multiple steps of operation, which could lead to excessive product loss and high production costs. Therefore, it is of importance to develop a fast and cost effective protein recovery method such as expanded bed adsorption chromatography (EBAC) to ensure a better and efficient recovery of protein, especially in large scale downstream process. In this study, thermal treatment of the Escherichia coli cell feedstock at 60oC for 30 min prior to solid removal in the conventional method has resulted in 1.4 times and 18% higher in purity and recovery yield respectively compared to non-heat-treated feedstock. In direct capture of HBcAg from unclarified feedstock using the STREAMLINE DEAE (weak anion-exchangers) in batch adsorption, heat treatment at 60oC for 45 min has increased the recovery yield and purity by 2.3 and 3.8 times respectively compared with non-heat-treated feedstock. When these conditions were applied in large scale purification of HBcAg via EBAC, the yield and purity have increased by 1.2 and 1.8 folds respectively, compared with that purified from non-heat-treated feedstock. Heating the crude feedstock has resulted in denaturation and precipitation of contaminants in the feedstock, hence reducing non-specific interactions between the cell debris and anion-exchanger. The present study has also demonstrated that purification of HBcAg from heat-treated unclarified feedstock was most efficient when EBAC operation using FastlineTM 20 contactor was operated at constant velocity (127.9 cm/h) in feedstock containing 5% of biomass. Although the current study showed that heat-treatment of unclarified feedstock could increase the purity of HBcAg and reduced non-specific binding of contaminant onto Streamline DEAE, the purity obtained was lower compared with that purified using conventional methods. Therefore, development of an affinity adsorbent using M13 phage bearing a disulfide constrained heptapeptide at the gpIII protein coat with the sequence, C-WSFFSNI-C as the ligand has been carried out in this study. M13 phage immobilised onto Streamline Base Matrix via epoxy activation was used in direct capture of HBcAg from unclarified feedstock via two different modes of EBAC operations; typical single pass operation and modified EBAC operation with recirculation of feedstock. Higher yield of HBcAg was obtained using modified EBAC operation due to increase in protein residence time in the column, however, the purity was reduced by 15% compared with typical EBAC operation, which could be due to diffusion of contaminants into the internal volume of the macroporous adsorbents. Although the purity of HBcAg recovered using M13 phage ligand adsorbents was higher (70-80%) but the yield was lower compared with that purified using anion-exchanger. Therefore, this study showed that peptide displayed on M13 phage can be employed as an affinity ligand in direct capture of HBcAg from unclarified feedstock using EBAC. When analysed with ELISA, the antigenicity of HBcAg purified using both adsorbents in EBAC was still preserved.